The dynamics of capital structure in transition economies - Eugene Nivorozhkin (Bank of Finland, Institute for Economies in Transition (BOFIT), 2003)
This paper uses a dynamic unrestricted capital structure model to examine the determinants of the private companies' target financial leverage and the speed of adjustment to it in two transition economies, the Czech Republic and Bulgaria.We explicitly model the adjustment of companies' leverage to a target leverage, and this target leverage is itself explained by a set of factors.The panel data methodology combines cross-section and time-series information.The results indicate that the Bulgarian corporate credit markets were less supply constrained than those of the Czech Republic during the period under investigation.Bulgarian companies adjusted much faster to the target leverage than Czech firms.The speed of adjustment related positively to the distance between target and observed ratio for Bulgarian companies while the relationship was neutral for Czech companies.The conservative policies of Czech banks and the exposure control were likely responsible for the slower adjustment among the larger companies while the opposite were true for Bulgarian banks and companies. G30, G32, O12, O52 capital structure; leverage; dynamic adjustment model; the Czech Republic; Bulgaria
URN:NBN:fi:bof-201408071998
Keywords: G30; G32; O12; O52; 330